Detection of Amblyogenic Refractive Error Using the Spot Vision Screener in Children. Issue 5 (May 2020) - Gaiser, Hilary; Moore, Bruce; Srinivasan, Gayathri; Solaka, Nadine; He, Ran
Abstract : SIGNIFICANCE: Vision screenings are conducted to detect significant refractive errors, amblyopia, and ocular diseases. Vision screening devices are desired to have high testability, sensitivity, and specificity. Spot has demonstrated high testability, but previous reports suggest that the Spot has low sensitivity for detecting amblyogenic hyperopia and moderate sensitivity for amblyogenic astigmatism. PURPOSE: This study assessed the concurrent validity of detecting amblyogenic refractive errors by the Spot (v.1.1.50; Welch Allyn Inc., Skaneateles Falls, NY) compared with cycloplegic retinoscopy. METHODS: A total of 475 subjects (24 to 96 months) were screened by Spot and then received a masked comprehensive examination. Sensitivity and specificity, Bland-Altman plot, receiver operating characteristic area under the curve, and paired t test were evaluated by comparing the results of the Spot (v1.1.50) using the manufacturer referral criteria with the results of the comprehensive examination using the 2013 American Association for Pediatric Ophthalmology and Strabismus criteria. RESULTS: The Spot (v.1.1.50) referred 107 subjects (22.53%) for the following: 18.73% (89/475) astigmatism, 4.63% (22/475) myopia, 0.42% (2/475) hyperopia, and 2.11% (10/475) anisometropia. The sensitivity and specificity of the Spot vision screener for detecting amblyogenic risk factors were 86.08% (95% confidence interval [CI], 76.45 to 92.84%) and 90.15% (95% CI, 86.78 to 92.90%). Areas under the curve were 0.906 (95% CI, 0.836 to 0.976) for hyperopia, 0.887 (95% CI, 0.803 to 0.972) for spherical equivalent, and 0.914 (95% CI, 0.866 to 0.962) for astigmatism. A modified hyperopia criteria cutoff of greater than +1.06 D improved the sensitivity from 25 to 80% with 90% specificity. The current cutoff criterion, greater than −1.75 D, for astigmatism seemed optimal. CONCLUSIONS: This study shows that the Spot vision screener accurately detects low spherical refractive errors and astigmatism. Lowering the hyperopia cutoff criteria from the current Spot screener referral criteria improves the sensitivity with desired (high) specificity.